The effects of production technologies on the air permeability and crack development of cross-laminated timber. (November 2019) - Kukk, Villu; Kalamees, Targo; Kers, Jaan
In a building envelope, the cross-laminated timber is often used as an air barrier layer. The objective of this study was to evaluate the impact of production technologies such as edge bonding, different initial moisture content of lamination and number of lamination layers (three and five) on the air permeability properties of the cross-laminated timber. Air leakage and crack area in cross-laminated timber panels were measured after the panels were conditioned in environments with different relative humidities in progressive steps from humid to dry environments (relative humidity 75% → relative humidity 43% → relative humidity 30% → relative humidity 15%). The test results showed that the five-layer specimens combined with initially drier laminations had the most considerable effect on avoiding air leakages through the panel. The greater number of layers helps to avoid any overlapping of gaps between laminations that are possible sources of air leakages. Based on the results, it is recommended to combine the technologies of using a larger number of layers together with initially drier laminations to minimise the growth of cracks on panel surfaces and avoid air leakages during the time of use.